(untitled) (Current Horticulture, 2024)
The experiment was conducted at Department of Horticulture, School of Agriculture, ITM University, Gwalior, to standardize the blended nectar of guava (Psidium guajava L.) and papaya (Carica papaya L.) pulp during 2021-2022. Blended drinks were good alternative for development of new products to provide benefit of taste, nutrition as well as medicinal properties. Due to high amount of ascorbic acid and fibre, guava acts as an anti-oxidant, whereas papaya is highly rich in carotenoides and riboflavin. The guava-papaya blended nectar was evaluated for its chemical and quality parameters at monthly interval for four months of storage period at ambient condition. The Total Soluble Solids, acidity, reducing sugars and total sugars were increased, whereas pH, ascorbic acid, non-reducing sugar and organoleptic score decreased with advancement in storage period in PET bottles. Nectar prepared with 20 % fruit pulp comprising 80 % guava and 20 % papaya with 13 % Total Soluble Solids (TSS), 0.3 % acidity and 70 ppm SO2 (T6) was found most acceptable (8.20) than other blend formulations. The nectar was organoleptically acceptable up to 4 months of storage at ambient temperature (18.3-27.90C) into PET bottles. Thus, guava and papaya can be utilized for valuable nectar beverage making which can be beneficial for the consumers in terms of taste, colour, flavour and therapeutic properties.